2021
DOI: 10.1186/s13638-020-01879-y
|View full text |Cite
|
Sign up to set email alerts
|

Body weight estimation of yak based on cloud edge computing

Abstract: In stock farming, the body size parameters and weight of yaks can reasonably reflect the growth and development characteristics, production performance and genetic characteristics of yaks. However, it is difficult for herders to measure the body size and weight of yaks by traditional manual methods. Fortunately, with the development of edge computing, herders can use mobile devices to estimate the yak’s body size and weight. The purpose of this paper is to provide a machine vision-based yak weight estimation m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…While this method effectively extracts the cattle's contours, variations in the cattle's standing posture can still impact the measurement results. Zhang et al (2021) [56] introduced a data-mining-based approach to estimate the body size of yaks. The results showed that this method was convenient and efficient, offering an effective means to measure the body size of yaks.…”
Section: Body Dimension Measurement Based On Color Image Sensing Datamentioning
confidence: 99%
“…While this method effectively extracts the cattle's contours, variations in the cattle's standing posture can still impact the measurement results. Zhang et al (2021) [56] introduced a data-mining-based approach to estimate the body size of yaks. The results showed that this method was convenient and efficient, offering an effective means to measure the body size of yaks.…”
Section: Body Dimension Measurement Based On Color Image Sensing Datamentioning
confidence: 99%
“…The experiment was conducted over four years, from 2017 to 2020. The grazing sheep and goat were two years old, with their initial body weight determined using a balance (33 kg on average), and the cattle body weight determined using the body measurements method (230 kg on average) (Zhang et al, 2021). A flock of six sheep or goats, or three cattle were placed in each paddock in each rotational grazing.…”
Section: Experimental Designmentioning
confidence: 99%
“…Moreover, the presented area can also be influenced by the distance between the camera equipment and the cows. Although the measurement of body size makes use of key areas or body parts like body width and height, heart girth, hip width, and height and thus achieves high accuracy, expensive equipment needs to be equipped at different aspects and angles accordingly, which is not applicable to housing farms (Qiao et al, 2019 ; Du et al, 2021 ; Zhang et al, 2021 ; Dang et al, 2022 ). Instead, the method integrating area and height takes advantage of three-dimensional size information of cows and becomes an accurate and reliable measurement, which is also consistent with the favorite indicators of experienced farmers for weight estimation artificially.…”
Section: Introductionmentioning
confidence: 99%